Laser-based Surface Modifications of Aluminum and its Alloys - Quazi, M.M.; Fazal, M.A.; Haseeb, A.S. Md. Abdul; Yusof, F.; Masjuki, Haji Hassan; Arslan, A. (Taylor & Francis, 2016)
Aluminum (Al) and its alloys have widespread engineering applications because of their higher strength to weight ratio, ductility, and formability. However, in various applications, mechanical properties such as hardness, corrosion, wear, and fatigue resistance are prerequisite at near surface regions. Such localized modification without affecting the bulk phase can be performed by various surface-engineering approaches including electro-deposition, physical and chemical vapor depositions, thermal spraying, plasma spraying, and organic polymeric coatings. Delamination failure of such coatings from the substrate is often inevitable due to the difference in film-to-substrate elastic modulus associated with the aforementioned processes. Recently, researchers have adopted a new approach of laser surface engineering to modify the near surface regions of metallic substrate by laser beams resulting in superior mechanical properties with the formation of novel microstructures. In this article, the recent developments in the surface modification of Al and its alloy by laser treatment are reviewed. Processing parameters and resulting microstructures of Al and its alloys are briefly summarized, along with their impact on mechanical properties. Finally, this article concludes future research directions.